Leading inter- and transdisciplinary research: Lessons from applying theories of change to a strategic research program - Deutsch, L.; Belcher, B.; Claus, R.; Hoffmann, S. (Elsevier, 2021)
Theory of Change (ToC) has been promoted as a useful tool in sustainability research for visioning, planning, communication, monitoring, evaluation and learning. It involves a mapping of steps towards a desired long-term goal supplemented with continuous reflection on how and why change is expected to happen in a particular context. However, there is limited reported experience with the development and application of ToCs in inter- and transdisciplinary research contexts. While some previous publications have focused on ex-post application, there has been little discussion about the process of developing and using ToCs in strategic planning and monitoring in large inter- and transdisciplinary research programs. This article reports challenges and lessons learned from the experience of developing and using ToCs in the inter- and transdisciplinary research program Wings (Water and sanitation innovations for non-grid solutions). Challenges include (1) managing time constraints, (2) balancing between concrete and abstract discussions, (3) ensuring diversity in group composition, (4) fluctuating between reservations and appreciation, and (5) fulfilling both service and science roles while leading the ToC process. The experience highlights the importance of alternating formal and informal interaction formats throughout the process, ensuring heterogenous group formation, involving early career scientists, being responsive to emergent needs and making the added value of developing and using ToCs explicit and tangible for all participants. Although these lessons are mainly derived from developing ToCs within the interdisciplinary program team, they can support other programs in both their inter- and transdisciplinary research endeavors.